Quantitative ethnopharmacological study of the Campidano Valley and Urzulei district, Sardinia, Italy. - Bruni, a; Ballero, M.; Poli, F. (Journal of ethnopharmacology, 1997)
A new method has been developed for quantitative, phytotherapeutical analysis with a goal to create a general tool suitable for a wide range of research situations. This tool would allow one to gather data in such a format as to facilitate comparison with studies from other areas. The method was applied to data gathered from two sites in Sardinia, Italy (Campidano and Urzulei). Analysis was performed on 2635 responses (a) by plant, (b) by plant part, (c) by medicinal preparation and (d) by therapeutic use. This yielded specificity indexes which proved useful in comparing phytotherapeutic applications in the two geographic areas under study. In Urzulei the original phytotherapeutic heritage is deeply rooted in the local socio-economic history and clearly reflects the area's geographic isolation. Indeed, in this area, there is little reliance on modern health care. On the other hand, in Campidano, the body of phytotherapeutic application is more extensive. Indeed, due to migration-and to a lesser extent isolation- the latter area has been more affected by technological interference and cultural overlapping. In this area attention is widely focused on such modern ailments as glycemia, hypertension and constipation.
The following values have no corresponding Zotero field: accession-num: 9254113
Keywords: Medicinal plants; Quantitative ethnopharmacology; Sardinia; Traditional phytotherapy

Quantitative ethnopharmacological study of the Campidano Valley and Urzulei district, Sardinia, Italy. - Bruni, a; Ballero, M; Poli, F (Journal of ethnopharmacology, 1997)
A new method has been developed for quantitative, phytotherapeutical analysis with a goal to create a general tool suitable for a wide range of research situations. This tool would allow one to gather data in such a format as to facilitate comparison with studies from other areas. The method was applied to data gathered from two sites in Sardinia, Italy (Campidano and Urzulei). Analysis was performed on 2635 responses (a) by plant, (b) by plant part, (c) by medicinal preparation and (d) by therapeutic use. This yielded specificity indexes which proved useful in comparing phytotherapeutic applications in the two geographic areas under study. In Urzulei the original phytotherapeutic heritage is deeply rooted in the local socio-economic history and clearly reflects the area's geographic isolation. Indeed, in this area, there is little reliance on modern health care. On the other hand, in Campidano, the body of phytotherapeutic application is more extensive. Indeed, due to migration-and to a lesser extent isolation- the latter area has been more affected by technological interference and cultural overlapping. In this area attention is widely focused on such modern ailments as glycemia, hypertension and constipation.
Keywords: Medicinal plants; Quantitative ethnopharmacology; Sardinia; Traditional phytotherapy